2017
DOI: 10.1002/humu.23362
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genetic architecture and phenotypic spectrum in the skeletal ciliopathies

Abstract: Defects in the biosynthesis and/or function of primary cilia cause a spectrum of disorders collectively referred to as ciliopathies. A subset of these disorders is distinguished by profound abnormalities of the skeleton that include a long narrow chest with markedly short ribs, extremely short limbs, and polydactyly. These include the perinatal lethal short-rib polydactyly syndromes (SRPS) and the less severe asphyxiating thoracic dystrophy (ATD), Ellis-van Creveld (EVC) syndrome, and cranioectodermal dysplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 100 publications
4
107
0
Order By: Relevance
“…Short‐rib thoracic dysplasia, also known as asphyxiating thoracic dysplasia (ATD) or Jeune syndrome (SRTD (MIM# 208500)), is an autosomal recessive skeletal ciliopathy characterized by narrow thoracic cage, short ribs, shortened tubular bones, and a trident acetabular roof, with or without polydactyly and in some individuals renal, liver, and retinal involvement (Schmidts et al., ). Many genes have been associated with SRTD (Huber & Cormier‐Daire, ; Zhang et al., ) but to date only two individuals are reported with skeletal ciliopathies and pathogenic variants in IFT81 (Duran et al., ). MED (MIM# 132400) is a heterogeneous disorder of the epiphyses in the long bones, due to autosomal dominant heterozygous mutations in COMP, COL9A1, COL9A2, COL9A3 , or MATN3 (Jackson et al., ) or autosomal recessive homozygous mutations in SLC26A2 (Makitie et al., ) and CANT1 (Balasubramanian et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Short‐rib thoracic dysplasia, also known as asphyxiating thoracic dysplasia (ATD) or Jeune syndrome (SRTD (MIM# 208500)), is an autosomal recessive skeletal ciliopathy characterized by narrow thoracic cage, short ribs, shortened tubular bones, and a trident acetabular roof, with or without polydactyly and in some individuals renal, liver, and retinal involvement (Schmidts et al., ). Many genes have been associated with SRTD (Huber & Cormier‐Daire, ; Zhang et al., ) but to date only two individuals are reported with skeletal ciliopathies and pathogenic variants in IFT81 (Duran et al., ). MED (MIM# 132400) is a heterogeneous disorder of the epiphyses in the long bones, due to autosomal dominant heterozygous mutations in COMP, COL9A1, COL9A2, COL9A3 , or MATN3 (Jackson et al., ) or autosomal recessive homozygous mutations in SLC26A2 (Makitie et al., ) and CANT1 (Balasubramanian et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, WES identified a homozygous missense variant (Chr11 (GRCh37) DYNC2H1 gene, with both parents being heterozygous carriers. This variant was previously reported in three patients with asphyxiating thoracic dysplasia (ATD) or short rib-polydactyly syndrome (SRPS) (Baujat et al, 2013;Dagoneau et al, 2009;Zhang et al, 2018). Particularly, only one 16-month-old patient (Baujat et al, 2013) had this variant in homozygosity; he showed clinical signs consistent with ATD as short ribs with narrow thorax, trident acetabular roof, long bones shortening, respiratory neonatal distress, long-term respirator complications, and short stature, so the DYNC2H1 variant was considered as disease causing by the authors.…”
Section: Resultsmentioning
confidence: 80%
“…Most of the reported cases were ATD patients (Baujat et al, ; Beales et al, ). p.gly241Arg has been found in ATD (Zhang et al, ), as well as in Verma‐Naumoff syndrome (Cavalcanti et al, ) and Majewski syndrome (Zhang et al, ), p.Thr365Ala has been associated with ATD and BLS, and p.Leu163IlefsTer7 with BLS (Zhang et al, )…”
Section: Molecular Resultsmentioning
confidence: 99%
“…IFT80 is known to be involved in other ciliopathies, essentially in Jeune asphyxiating thoracic dysplasia (ATD) (Baujat et al, ; Beales et al, , 80; Zhang et al, ), but also in Verma‐Naumoff syndrome (Cavalcanti et al, ). Verma‐Naumoff syndrome has recently been subcategorized with Saldino‐Noonan syndrome as a single SRPS (SRPS Type I/III) by the current nosology (Bonafe et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation